Companion Animals and Domestic Violence Rescuing Me, Rescuing You - Taylor, Nik.; Fraser, Heather; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this book, Nik Taylor and Heather Fraser consider how we might better understand human-animal companionship in the context of domestic violence. The authors advocate an intersectional feminist understanding, drawing on a variety of data from numerous projects they have conducted with people, about their companion animals and links between domestic violence and animal abuse, arguing for a new understanding that enables animals to be constituted as victims of domestic violence in their own right. The chapters analyse the mutual, loving connections that can be formed across species, and in households where there is domestic violence. Companion Animals and Domestic Violence also speaks to the potentially soothing, healing and recovery oriented aspects of human-companion animal relationships before, during and after the violence, and will be of interest to various academic disciplines including social work, anthropology, sociology, philosophy, geography,as well as to professionals working in domestic violence or animal welfare service provision. .
Keywords: Social structure; Equality; Ethnology; Criminal behavior; Animal welfare -- Moral and ethical aspects; Social Structure; Sociocultural Anthropology; Criminal Behavior; Animal Ethics